(untitled) (Research, Society and Development, 2022)
Delirium in adults admitted to an intensive care unit may be related to mechanical ventilation, the use of sedatives and prolonged ICU stay, being associated with worse clinical conditions and hospital outcomes. Objectives: to investigate the diagnosis of delirium in ICU patients and how it influences the admission of these patients. Methodology: an integrative and exploratory review study. A search for studies was performed in the MEDLINE, PubMed and LILACS databases, with the following descriptors: delirium and ICU and mechanical ventilation and diagnosis. Results: 14 studies were included, being: 5 carried out in Europe, 4 in Asia, 2 in North America and 1 in South America, in addition to two bicentric studies. The severity of the dysfunction is related to older patients, with longer mechanical ventilation, longer sedation and days of hospitalization. Among the diagnostic assessment instruments, the Confusion Assessment Method for Intensive Care Unit (CAM-ICU) obtained a satisfactory response among the analyzed studies. Conclusion: the most effective strategy to reduce delirium is primary prevention, such as investment in human resources, use of non-pharmacological measures and changes in the management of the dysfunction. The correct and early diagnosis of delirium can have a positive impact on the prognosis of patients in the ICU, reducing the organic repercussions and morbidity and mortality of these patients.